Assessment of antibiotic consumption patterns in hospital and primary healthcare using WHO Access, Watch and Reserve classification (AWaRe) in Sichuan Western China: 2020 - Haoxin Song; Xiao Liu; Kun Zou; Hailong Li; Haotian Fei; Liang Huang; Qin Yu; Lingli Zhang (BMC, 2024)
Abstract Background The Access, Watch, and Reserve (AWaRe) classification of antibiotics was a useful tool to support antibiotic stewardship. However, the AWaRe patterns of antibiotic consumption in Western China were unclear. We aimed to assess the antibiotic consumption patterns using the AWaRe Classification of public hospitals in Sichuan Province Western China. Methods Antibiotic consumption data of year 2020 were obtained from the Sichuan Province Drug Use Monitoring Platform. We measured the antibiotic consumption (DDDs per 1,000 inhabitants per day, DIDs), calculated the proportion of antibiotic use, the ratio of Access to Watch antibiotics and patterns of antibiotic use by using drug utilization 90%. Results This analysis included 4452 public health institutions. The antibiotic consumption rate was 10.39 DIDs (Median 8.50, IQR 7.71-12.96). The proportions of Access antibiotic use and Watch antibiotic use were 46.83% (Median 47.49, IQR 44.16-52.02) and 51.20% (Median 51.43, IQR 45.42-54.61), respectively. The Access-to-Watch index was 0.91 (Median 0.92, IQR 0.81-1.15). Amoxicillin (16.85%), cefuroxime (9.21%), cefixime (8.60%%), levofloxacin (8.11%) and metronidazole (6.16%) were the most consumed antibiotics. Conclusions The proportion of Access antibiotic consumption in Sichuan Western China has not achieved the WHO target of 60%. Overuse of antibiotic is serious in Sichuan. National and regional antibiotics management systems, stewardship programs and surveillance of antibiotic consumption based on AWaRe classification are needed to improve antibiotic consumption patterns, curb antibiotic overuse and combat antimicrobial resistance in Western China.